Recurrent infections with IgG2 deficiency. Issue 7 (July 1985) - Plebani, A; Duse, M; Monafo, V
Abstract : An 11 year old girl with retarded growth, recurrent infections, bronchiectasis, and normal serum immunoglobulin concentrations had a combined deficit of the IgG2 subclass and IgG and IgM specific antibodies. Immunoglobulin replacement was followed by clinical improvement. The importance of determining both IgG subclasses and antibody activity in patients with recurrent infections and normal serum immunoglobulin values is emphasised.